FOXO3 Transcription Factor Regulates IL-10 Expression in Mycobacteria-Infected Macrophages, Tuning Their Polarization and the Subsequent Adaptive Immune Response - Bouzeyen, Rania; Haoues, Meriam; Barbouche, Mohamed-Ridha; Singh, Ramandeep; Essafi, Makram (Frontiers in Immunology, 2019)
Alveolar Macrophages play a key role in the development of a robust adaptive immune response against the agent of Tuberculosis (TB), Mycobacterium tuberculosis (M.tb). However, macrophage response is often hampered by the production of IL-10, a potent suppressor of the host immune response. The secretion of IL-10 correlates with TB pathogenesis and persistence in host tissues. Concordantly, inhibition of IL- 10 signaling, during BCG vaccination, confers higher protection against M.tb through a sustained Th1 and Th17 responses. Therefore, uncovering host effectors, underlying mycobacteria-induced expression of IL-10, may be beneficial toward the development of IL-10-blocking tools to be used either as adjuvants in preventive vaccination or as adjunct during standard treatment of TB. Here, we investigated the role of FOXO3 transcription factor in mycobacteria-induced secretion of IL-10. We observed that PI3K/Akt/FOXO3 axis regulates IL-10 expression in human macrophages. Knocking down of FOXO3 expression resulted in an increase of IL-10 production in BCG-infected macrophages. The gene reporter assay further confirmed the transcriptional regulation of IL-10 by FOXO3. In silico analysis identified four Forkhead binding motifs on the human IL-10 promoter, from which the typical FOXO3 one at position -203 was the major target as assessed by mutagenesis and CHIP binding assays. Further, we also observed a decrease in gene expression levels of the M1 typical markers (i.e CD80 and CD86) in SiFOXO3-transfected macrophages while activation of FOXO3 led to the increase in the expression of CD86, MHCI and MHCII. Finally, co-culture of human lymphocytes with siFOXO3-transfected macrophages, loaded with mycobacterial antigens, showed decreased expression of Th1/Th17 specific markers and a simultaneous increase in expression of IL-4 and IL-10. Taken together, we report for the first time that FOXO3 modulates IL-10 secretion in mycobacteria-infected macrophage, driving their polarization and the subsequent adaptive immune response. This work proposes FOXO3 as a potential target for the development of host-directed strategies for better treatment or prevention of TB